Oxidation of threo‐9, 10‐Dihydroxystearic Acid Mediated by Micrococcus luteus as a Key Step in the Conversion of Oleic Acid into Pelargonic and Azelaic Acids. Issue 14 (28th May 2021) - Colombo, Danilo; Brenna, Elisabetta; Casali, Beatrice; Ghezzi, Maria Chiara; Parmeggiani, Fabio; Tentori, Francesca; Tessaro, Davide; Boratyński, Filip
Abstract: A sequential one‐pot chemoenzymatic procedure for the conversion of diol 1, easily obtained from oleic acid, into pelargonic and azelaic acids is herein described. The oxidation of diol 1 into a mixture of the corresponding regioisomeric hydroxyketones was promoted by an alcohol dehydrogenase from Micrococcus luteus, selected after an extensive screening of commercial enzyme kits and strain collections. The stereochemistry of the oxidation process of chiral diol 1 was also investigated. The hydroxyketones obtained by the biocatalyzed oxidation were submitted to further oxidative cleavage by a mild treatment with aqueous NaClO in a biphasic mixture, affording pelargonic and azelaic acids in high yield (76 and 71 %, respectively) with no need of column chromatography. Abstract : Biocatalysis : Pelargonic and azelaic acids can be obtained from threo ‐9, 10‐dihydroxystearic acid by a sequential one‐pot chemo‐enzymatic process, combining Micrococcus luteus – mediated oxidation and aq. NaClO 10 % oxidative cleavage. A simple work‐up procedure allows the isolation of the final acids as separated compounds without using column‐chromatography.